Obesity and Cytokines in Childhood-Onset Systemic Lupus Erythematosus. (3rd March 2014) - Sinicato, Nailú Angélica; Postal, Mariana; Peres, Fernando Augusto; Peliçari, Karina de Oliveira; Marini, Roberto; dos Santos, Allan de Oliveira; Ramos, Celso Dario; Appenzeller, Simone
Abstract : Background . In systemic lupus erythematosus (SLE), atherosclerosis is attributed to traditional and lupus related risk factors, including metabolic syndrome (MetS), obesity, and inflammation. Objective . To evaluate the association between obesity, measures of body fat content, serum tumor necrosis factor alpha (TNF-α ), and interleukin (IL)-6 and -10 levels in childhood-onset SLE (cSLE). Methods . We screened consecutive cSLE patients followed up in the Pediatric Rheumatology Outpatient Clinic of the State University of Campinas. cSLE patients were assessed for disease and damage. Obesity was definite as body mass index (BMI) ≥30 kg/m 2 . Serum TNF-α, IL-6, and IL-10 levels were measured by ELISA. Dual-energy X-ray absorptiometry was used to determine total fat mass, lean mass, and percent of body fat. Results . We included 52 cSLE patients and 52 controls. cSLE patients had higher serum TNF-α ( P = 0.004 ), IL-6 ( P = 0.002 ), and IL-10 ( P < 0.001 ) levels compared to controls. We observed higher serum TNF-α ( P = 0.036 ) levels in cSLE patients with obesity. An association between serum TNF-α levels and body fat percent ( P = 0.046 ) and total fat mass on trunk region ( P = 0.035 ) was observed. Conclusion . Serum TNF-α levels were associated with obesity and body fat content in cSLE. Our finding suggests that obesity may contribute to the increase of serum TNF-α levels in cSLE.